2017
DOI: 10.1182/bloodadvances.2017004671
|View full text |Cite
|
Sign up to set email alerts
|

Human and murine splenic neutrophils are potent phagocytes of IgG-opsonized red blood cells

Abstract: Key Points• In steady state, where no IgGs against RBCs are present, macrophages are the primary phagocytes of RBCs.• In conditions where RBCs are IgGopsonized, neutrophils can have a major effect on RBC clearance.Red blood cell (RBC) clearance is known to occur primarily in the spleen, and is presumed to be executed by red pulp macrophages. Erythrophagocytosis in the spleen takes place as part of the homeostatic turnover of RBCs to remove old RBCs. It can be strongly promoted by immunoglobulin G (IgG) opsoniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
40
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 47 publications
5
40
0
2
Order By: Relevance
“…In contrast, antibodies against RhD and RhCE failed to demonstrate significant rigidification of human RBCs, consistent with prior literature. 31 Antibodies against GPA and RhD can produce markedly different effects on different subsets of phagocytic cells, 48 and, although the authors hypothesized that copy number was critical, the current findings suggest that altered deformability may have also been contributory. The precise function of RhCE has been difficult to define 49 and a large diversity of polymorphisms has been described.…”
Section: Discussionmentioning
confidence: 59%
“…In contrast, antibodies against RhD and RhCE failed to demonstrate significant rigidification of human RBCs, consistent with prior literature. 31 Antibodies against GPA and RhD can produce markedly different effects on different subsets of phagocytic cells, 48 and, although the authors hypothesized that copy number was critical, the current findings suggest that altered deformability may have also been contributory. The precise function of RhCE has been difficult to define 49 and a large diversity of polymorphisms has been described.…”
Section: Discussionmentioning
confidence: 59%
“…12 Possibly, neutrophils may also play a role in the uptake of IgG-opsonized blood cells because neutrophils from the human spleen were shown to be highly potent in the phagocytosis of erythrocytes opsonized with high concentrations of murine IgG antibodies. 28 However, neutrophils were not capable of phagocytozing anti-RhD opsonized erythrocytes. 28 Because we have only tested phagocytosis by red pulp macrophages with anti-RhD-opsonized erythrocytes, we cannot be sure that our findings can be extrapolated to other opsonized antigens or blood groups.…”
Section: Discussionmentioning
confidence: 99%
“…28 However, neutrophils were not capable of phagocytozing anti-RhD opsonized erythrocytes. 28 Because we have only tested phagocytosis by red pulp macrophages with anti-RhD-opsonized erythrocytes, we cannot be sure that our findings can be extrapolated to other opsonized antigens or blood groups. However, we have previously shown that different antibodies and antigens showed similar results in erythrophagocytosis by monocyte-derived macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, although the latter is a clear example of (antigen-specific) “immunosuppression,” it is not generally considered to be a type of TRIM. RBC transfusions also affect innate immunity, with specific effects on macrophages, dendritic cells, and granulocytes [22, 23]. Of course, because of crosstalk mechanisms, it is not surprising that effects on innate immunity also influence adaptive immune responses [22, 24].…”
Section: Text Of the Reviewmentioning
confidence: 99%
“…Taken together, these outcomes could produce a TRIM effect of enhancing post-surgical or nosocomial bacterial infection rates and severity [42]. In addition, ingestion of (antibody-coated) RBCs by splenic granulocytes [23] can impair oxidative-burst function [41], thereby potentially impairing this type of protection against invading blood-borne pathogens.…”
Section: Text Of the Reviewmentioning
confidence: 99%